“Person” in the Polish Family and Guardianship Code - Szczot, Elżbieta (Philosophy and Canon Law, 2021)
The article presents the issues related to the understanding of the person in the Polish Family and Guardianship Code. It shows the complex issue of acquiring legal capacity, including the legal capacity of the conceived child, the relation between parental authority and the child, adoption of the child, the acquisition and scope of capacity for legal acts, as well as some limitations resulting from incapacitation were showed.